T. S. Eliot's Ariel Poems Making Sense of the Times - Budziak, Anna (Taylor & Francis, 2022)
What T. S. Eliot once said about Shakespeare and Dante-noting that that the supreme poet "in writing himself, writes his time"-fittingly characterises his own work, also including The Ariel Poems with which he responded, promptly and pointedly, to the problems of the times. Published with unwavering regularity, a poem a year, they were composed in this period when Eliot was mainly writing prose; and, like his prose, they reverberated with various contemporary issues ranging from the revision of the Book of Common Prayer to translations of Heidegger to the questions of leadership and populism. This study, in order to highlight the historical specificity of the poems, or, their topicality, traces the constellations of thought linking Eliot's prose and poetry. Additionally, it attempts to expose the Ariels' shared arc of meaning-the unobtrusive incarnational metaphor which determines the perspective from which they propose a specific understanding of the epoch, the underlying figure of thought which brings them together into a conceptually discrete set. It is the first study that endeavours to both universalize and historicise the series, striving to disclose the regular without suppressing the random. Approaching the series as a system of orderly disorder, the notion very much at home with chaos theory, it offers interpretations that are either fresh, or significantly reangled, and suggests new intellectual contexts.